Holistic face perception is impaired in developmental prosopagnosia. (November 2018) - Towler, John; Fisher, Katie; Eimer, Martin
Abstract: Individuals with developmental prosopagnosia (DP) have severe difficulties recognising familiar faces. A current debate is whether these face recognition impairments derive from problems with face perception and in particular whether individuals with DP cannot utilize holistic representations of individual faces. To assess this hypothesis, we recorded event-related potentials (ERPs) during a sequential face identity matching task where successively presented pairs of upright faces were either identical or differed with respect to their internal features, their external features, or both. Participants with DP and age-matched controls reported on each trial whether the face pair was identical or different. To track the activation of cortical visual face memory representations, we measured N250r components over posterior face-selective regions. N250r components to full face repetitions were strongly attenuated for DPs as compared to control participants, indicating impaired face identity matching processes in DP. In the Control group, the N250r to full face repetitions was superadditive (i.e., larger than the sum of the two N250r components to partial repetitions of external or internal features). This demonstrates that holistic face representations were involved in identity matching processes. In the DP group, N250r components to full and partial identity repetitions were strictly additive, indicating that the identity matching of external and internal features operated in an entirely part-based fashion, without any involvement of holistic representations. In line with this conclusion, DPs also made a disproportionate number of errors on partial repetition trials, where they often failed to report a change of internal facial features. This suggests an atypical strategy for encoding external features as cues to identity in DP. These results provide direct electrophysiological and behavioural evidence for qualitative differences in the representation of face identity in the occipital-temporal face processing system in developmental prosopagnosia.